HIV and viral hepatitis coinfection analysis using surveillance data from 15 US states and two cities. Issue 7 (11th April 2018) - Bosh, K. A.; Coyle, J. R.; Hansen, V.; Kim, E. M.; Speers, S.; Comer, M.; Maddox, L. M.; Khuwaja, S.; Zhou, W.; Jatta, A.; Mayer, R.; Brantley, A. D.; et al.
Abstract: Coinfection with human immunodeficiency virus (HIV) and viral hepatitis is associated with high morbidity and mortality in the absence of clinical management, making identification of these cases crucial. We examined characteristics of HIV and viral hepatitis coinfections by using surveillance data from 15 US states and two cities. Each jurisdiction used an automated deterministic matching method to link surveillance data for persons with reported acute and chronic hepatitis B virus (HBV) or hepatitis C virus (HCV) infections, to persons reported with HIV infection. Of the 504 398 persons living with diagnosed HIV infection at the end of 2014, 2.0% were coinfected with HBV and 6.7% were coinfected with HCV. Of the 269 884 persons ever reported with HBV, 5.2% were reported with HIV. Of the 1 093 050 persons ever reported with HCV, 4.3% were reported with HIV. A greater proportion of persons coinfected with HIV and HBV were males and blacks/African Americans, compared with those with HIV monoinfection. Persons who inject drugs represented a greater proportion of those coinfected with HIV and HCV, compared with those with HIV monoinfection. Matching HIV and viral hepatitis surveillance data highlights epidemiological characteristics of persons coinfected and can be used to routinely monitor health status and guide state and national public health interventions.